Digital Health Communication on Instagram: Social Media and Breastfeeding Education in Indonesia - Utami, Nadia Wasta; Wingi, Syanthia (Department of Communications, Universitas Islam Indonesia, 2025)
This research examines the role of Instagram as a platform for digital health communication concerning breastfeeding education in Indonesia. The study centers on four Instagram accounts with diverse orientations: @aimi_asi (a non-profit organization), @momuung.id (a commercial enterprise), and two personal accounts, @stephanieking (breastfeeding and lactation consultant) and @brendashahnaz (healthcare professionals). Utilizing qualitative analysis, the investigation explores the studied social media’s post characteristics, from post content, post form, to post delivery. The results indicate that both institutional and personal accounts actively participate in health education by employing multimodal content, which includes informational posts, instructional videos, and personal narratives. All accounts adopt affective and participatory approaches that blend emotional storytelling with evidence-based information. Specifically, the first account by AIMI ASI emphasizes the economic and environmental sustainability aspects of breastfeeding, whereas Momuung.id combines health awareness with product promotion. In contrast, the personal accounts leverage authenticity and lived experience to craft relatable maternal narratives that enhance emotional connection and foster community engagement. The analysis reveals that these digital platforms exemplify a hybrid communication model that integrates medical knowledge, emotional empathy, and cultural values within the collective contexts of everyday life in Indonesia. This hybrid approach transforms breastfeeding advocacy from a hierarchical public health initiative into a participatory, community oriented dialogue. The study contributes to broadening non-Western perspectives within digital health communication scholarship by highlighting the significance of cultural sensitivity, emotional resonance, and trustbuilding in shaping effective digital health discourse. Ultimately, Instagram functions as both an informational and affective ecosystem that promotes maternal health literacy and facilitates social empowerment through networked communication.